Determinants of income smoothing practices : evidence from South East Asia countries / Wan Adibah Wan Ismail, Khairul Anuar Kamarudin and Muhd Kamil Ibrahim - Wan Ismail, Wan Adibah; Kamarudin, Khairul Anuar; Ibrahim, Muhd Kamil (Institute of Research, Development and Commercialization (IRDC), 2005)
This paper presents the findings of a comparative study of income smoothing practices in Malaysia, Indonesia, Singapore, Philippines and Thailand. The objective of this study is to identify the factors associated with the incidence of income smoothing in these countries. The sample comprises 1,028 listed companies during the period 1999 to 2003. Five hypotheses, which relate income smoothing to company age, growth, size, leverage and earnings are tested in the study. Descriptive statistics indicate that income smoothing is practiced in South-east Asia countries.